KARAKTERISTIK SULAMAN BENANG EMAS PADA BAJU PENGANTIN TRADISIONAL MINANGKABAU DI KECAMATAN LUBUK BEGALUNG - Yuliarma, Yuliarma; Ismalita, Villia Nur (Gorga : Jurnal Seni Rupa, 2023)
The purpose of the research is to describe The characteristics of the motif design include the shape of the motif, the decorative pattern, and the placement of the motif on the gold thread embroidered product which is applied to traditional Minangkabau wedding dresses in the industrial center of Lubuk Begalung District, Padang. Traditional motif designs that are applied to gold thread embroidered wedding dress products at the of Lubuk Begalung Padang Industrial center has the characteristics their distinguish them from embroidery from other regions. This research used a qualitative descriptive method with the type of data required in the form of primary data and secondary data. The data were collected through observation, interviews, and documentation studies. The characteristics of the traditional Minangkabau gold thread embroidery design is in the form of naturalist motifs such as the kaluak babungo motif, peacock, hong bird, orchid flower, and sponge. The decorative patterns used are free decorative patterns, sow decorative patterns, hanging decorative patterns, and walking fringe decorative patterns. The placement of the motif includes the neckline, the ends of the sleeves, on the bottom edge of the front and back clothes.Keywords: gold thread embroidery, wedding dress. AbstrakPenelitian ini bertujuan untuk mendeskripsikan karakteristik desain motif meliputi bentuk motif, pola hias, dan penempatan motif pada produk sulaman benang emas yang diterapkan pada baju pengantin tradisional Minangkabau di sentra industri Kecamatan Lubuk Begalung Padang. Desain motif tradisional yang di terapkan pada produk  baju pengantin sulaman benang emas di sentra Industri Lubuk Begalung Padang memiliki ciri khas yang membedakannya dengan sulaman dari daerah lain.  Penelitian ini menggunakan metode deskriptif kualitatif dengan jenis data yang diperlukan berupa data primer dan data sekunder. Data yang dikumpulkan melalui teknik observasi, wawancara, dan studi dokumentasi. Ciri khas desain motif sulaman benang emas tradisional Minangkabau berupa bentuk motif naturalis seperti motif kaluak babungo, burung merak, burung hong, bunga anggrek, dan bunga karang. Pola hias yang digunakan pola hias bebas, pola hias tabur, pola hias menggantung, dan pola hias pinggiran berjalan. Penempatan motif meliputi garis leher, ujung lengan, pada pinggir bawah baju depan dan belakang.Kata Kunci: sulaman benang emas, baju pengantin. Authors:Yuliarma : Universitas Negeri PadangVillia Nur Ismalita : Universitas Negeri Padang References:Ibrahim, A., Djafri, D., Bafiman, B., Yanis, M., Alimunar, A., Ilyas, M., & Akbar, R. (1986). Pakaian adat tradisional daerah Sumatera Barat.Pulukadang, Roesbani. (2009). Keterampilan Menhias Kain. Bandung: Angkasa.Riza Mutia. (2012). Ragam Hias pada Koleksi Museum Adityawarman. Padang.Rosma. (1997). Nukilan Bordir Sumatra Barat. Cipta Budaya Indonesia.Suhersono, Hery. (2006). Desain Bordir Motif Batik. Jakarta. PT. Gramedia Pustaka Utama.UTARI, A. G., Zahri, W., & Idrus, Y. (2014). Studi Tentang Kerajinan Sulaman Benang Emas di Nagari Saniangbaka Kecamatan X Koto Singkarak Kabupaten Solok. Journal of Home Economics and Tourism, 7(3). (http://ejournal.unp.ac.id/index.php/jhet/article/view/4324).Yuliarma. (2018). Model Of Embroidery Design ˜Kepala Peniti™ Minangkabau On Acculturative Batik. Vol 301 Seventh International Conference on Languanges and Arts (ICLA).  (http://repostory.unp.ac,id/21978/1/EMBROIDERY%2DESIGN%200K.pdf).Yuliarma, Y. DESIGN CHARACTERISTICS OF NATURAL MOTIVES IN VARIOUS DECORATIVE AND MINANGKABAU TRADITIONAL EMBROIDERY.(http://repostory.unp.ac,id/21978/1/EMBROIDERY%2DESIGN%200K.pdf).Yuliarma, Y. (2019, March). Model of Embroidery Design ˜Kepala Peniti'Minangkabau on Acculturative Batik. In Seventh International Conference on Languages and Arts (ICLA 2018) (pp. 128-135). Atlantis Press. (https://www.atlantis-press.com/proceedings/icla-18/55914482).Yuliarma, Y. (2014). STUDI TENTANG DISAIN RAGAM HIAS PAKAIAN PENGANTIN TRADISIONAL LUBUK BEGALUNG PADANG. (Journal of Home Economics and Tourism, 6(2).(http://ejournal.unp.ac.id/index.php/jhet/article/view/3422).Yuliarma, Yuliarma (2021) Sulaman Benang Emas Tradisional Minangkabau. In: Sulaman Benang Emas Tradisional Minangkabau. UPTD Meseum Adityawarman, Padang, pp. 1-110. (http://repository.unp.ac.id/39133/).Yuliarma. (2013). Disain Ragam Hias. UNP.Riza Mutia. (2012). Ragam Hias pada Koleksi Museum Adityawarman. Padang.Rosma. (1997). Nukilan Bordir Sumatra Barat. Cipta Budaya Indonesia.